Optimizing Nodal, Wnt and BMP signaling pathways for robust and efficient differentiation of human induced pluripotent stem cells to intermediate mesoderm cells - Magro-Lopez, Esmeralda; Vazquez-Alejo, Elena; Espinar-Buitrago, María de la Sierra; Muñoz-Fernández, María Ángeles (Frontiers in Cell and Developmental Biology, 2024)
Several differentiation protocols have enabled the generation of intermediate mesoderm (IM)-derived cells from human pluripotent stem cells (hPSC). However, the substantial variability between existing protocols for generating IM cells compromises their efficiency, reproducibility, and overall success, potentially hindering the utility of urogenital system organoids. Here, we examined the role of high levels of Nodal signaling and BMP activity, as well as WNT signaling in the specification of IM cells derived from a UCSD167i-99-1 human induced pluripotent stem cells (hiPSC) line. We demonstrate that precise modulation of WNT and BMP signaling significantly enhances IM differentiation efficiency. Treatment of hPSC with 3 μM CHIR99021 induced TBXT+/MIXL1+ mesoderm progenitor (MP) cells after 48 h of differentiation. Further treatment with a combination of 3 μM CHIR99021 and 4 ng/ml BMP4 resulted in the generation of OSR1+/GATA3+/PAX2+ IM cells within a subsequent 48 h period.Molecular characterization of differentiated cells was confirmed through immunofluorescence staining and RT-qPCR. Hence, this study establishes a consistent and reproducible protocol for differentiating hiPSC into IM cells that faithfully recapitulates the molecular signatures of IM development. This protocol holds promise for improving the success of protocols designed to generate urogenital system organoids in vitro, with potential applications in regenerative medicine, drug discovery, and disease modeling.